React 16 essentials : a fast-paced, hands-on guide to designing and building scalable and maintainable web apps with React 16 - Fedosejev, Artemij; Boduch, Adam (Packt Publishing, 2017)
Everything you need to start working with React 16 and assess React Fiber About This Book Hands-on examples and tutorials for the latest React 16 release Assess the impact of React Fiber for your future web development Build maintainable and high performance React 16 web applications Who This Book Is For If you're a frontend developer with some knowledge of native JavaScript development and frontend frameworks, wishing to learn the fastest web user interface library there is, then this book is ideal for you. What You Will Learn Learn to code React 16 with hands-on examples and clear tutorials Install powerful React 16 tools to make development much more efficient Understand the impact of React Fiber today and the future of your web development Utilize the Redux application architecture with your React components Create React 16 elements with properties and children Get started with stateless and stateful React components Use JSX to speed up your React 16 development process Add reactivity to your React 16 components with lifecycle methods Test your React 16 components with the Jest test framework In Detail React 16 Essentials, Second Edition, fully updated for React 16, takes you on a fast-paced journey through building your own maintainable React 16 applications. React experts Artemij Fedosejev and Adam Boduch give you all the essentials you need to know and start working with React 16, in this new edition of the best-selling React.js Essentials title. You'll find the latest React 16 code updates, assessment of React Fiber, new coverage of Redux, and how to work as a modern React developer. The authors offer you their current assessment of React Fiber, and you'll soon be exploring React 16 hands on, creating your own single and multiple user interface elements with React 16. You'll then see how to create stateless and stateful components and make them reactive. You'll also learn to interact between your components and lifecycle methods, and gauge how to effectively integrate your user interface components with other JavaScript libraries. Delve deep into the core elements of the Redux architecture and learn how to manage your application and data persistence. Then go the extra mile with the Jest test framework, and run multiple tests on your applications and find solutions to scale without complexity. Today React is used by Facebook, Instagram, Khan Academy, and Imperial College London, to name a few. Many new users recognize the benefits of R ...